SWOT Analysis of Lending Platform from Blockchain Technology Perspectives - Wisnu Uriawan (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2020)
Blockchain Technology become phenomenal issue in the world, emerging with bitcoin and IoT. It had been implemented in many areas in human activity. Advantages of blockchain technology is distributed ledger where resources distributed to all member in network. Loans or credit as part of human activity in their life. When we need cash for a major expense, it might be tempting to borrow from a payday lender or max out a credit card or similar, but you have other options that will not harm your credit or put you in a cycle of debt, even if your credit record is not all that great. Collateral loans could be a way to borrow the money as you need. One of which is the lending platform. Blockchain technology has been implemented in many lending platforms, but there are still any weaknesses that can be refined and optimized. Tool of analysis is SWOT, describes of four analysis, as follow: Strength, Weakness, Opportunity and Threats. This paper purpose to analyzed lending platform measured by look for the weaknesses variable and how to optimize that system performance that can improve for helping people in lending process. In addition, the result of this analysis can use for enhancement recommendation the system based on the weaknesses are found and opportunity for make a lending platform robust.